1991
DOI: 10.1097/00001888-199111000-00013
|View full text |Cite
|
Sign up to set email alerts
|

A review of studies concerning effects of sleep deprivation and fatigue on residentsʼ performance

Abstract: Possible effects of sleep deprivation and fatigue on the performance and well-being of residents have received little scientific examination until recently. This article is a review of the studies on this topic published since 1970. All those studies that dealt with residents' moods and attitudes demonstrated deleterious effects of sleep deprivation and fatigue. The implications of this finding for patient care deserve exploration. Residents' acuity on performance tests requiring prolonged vigilance tended to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
0
9

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(153 citation statements)
references
References 0 publications
3
141
0
9
Order By: Relevance
“…2,3 Paradoxically, in the natural environment there are well-documented deficits in decision making due to sleep deprivation. 4,5 In emergency response, disaster management, military encounters, and other fast-paced situations with uncertain outcomes and imperfect information, good decision making is significantly hampered by sleep deprivation. [6][7][8] Although the lapses of sustained attention that are characteristic of sleep deprivation contribute to errors and accidents, 3,8 attentional lapses are not the whole story of sleep deprivation effects on naturalistic decision making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Paradoxically, in the natural environment there are well-documented deficits in decision making due to sleep deprivation. 4,5 In emergency response, disaster management, military encounters, and other fast-paced situations with uncertain outcomes and imperfect information, good decision making is significantly hampered by sleep deprivation. [6][7][8] Although the lapses of sustained attention that are characteristic of sleep deprivation contribute to errors and accidents, 3,8 attentional lapses are not the whole story of sleep deprivation effects on naturalistic decision making.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Paradoxically, in the natural environment there are well-documented deficits in decision making due to sleep deprivation. 4,5 In emergency response, disaster management, military encounters, and other fast-paced situations with uncertain outcomes and imperfect information, good decision making is significantly hampered by sleep deprivation. …”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This heightened attention has been driven by a growing body of literature on the deleterious effects of sleep deprivation on residents' wellbeing and performance. 2,3,[7][8][9][10] Studies have identified many domains affected by fatigue, including professionalism, learning, errors, and completion of complex cognitive tasks. [11][12][13] The increased incidence of postcall automobile accidents among interns and residents is well documented.…”
Section: Introductionmentioning
confidence: 99%
“…25,31,34 Also, there has been significant interest in the impact of fatigue on surgical skills. Much of the literature supporting a decrease in physical skill and ability cited by the ACGME in the initiation of DHR was based on studies conducted in nonsurgeons (military personnel and college-aged volunteers) in the self-promoted sleep science literature.…”
Section: Technique/trainingmentioning
confidence: 99%